Systematic Literature Review (SLR) Makna Halalan Thayyiban Bagi Konsumen Muslim pada Produk Makanan di Kabupaten Gresik: Studi Fenomenologi di Toko UD Adji Jaya Makmur - Walid In'am Ahmad; Iskandar Ritonga; Mugiyati; Lilik Rahmawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Halalan thayyiban is an important legitimacy that must be owned by every business, especially in food products or products such as beauty and so on as a benchmark for safety and to increase consumer awareness of the importance of using products that already have halal certification and food labeling logos greatly affect the quality of the product. This study aims to determine how the public's perception, especially for Muslim consumers, is in understanding or interpreting food products that are halal thayyiban and how to solve problems related to challenges and opportunities faced by Indonesia in halal certification of food products that are in accordance with applicable BPJPH or LPH regulations. This study uses the SLR paradigm approach or systematic literature review obtained from journals that have been published from 2015 to 2024 after being traced, the results obtained show that there is still a lack of public understanding of the importance of halal certification for a food product because many people still think that food products that do not contain pork, alcohol and the like are included in products that are halal for consumption, but halal standardization is not only seen in terms of product ingredients but also from the production process of using clean kitchen utensils, kitchen sanitation or clean production areas and the like which are very important aspects in assessing the halal standardization of food products that are in accordance with applicable procedures and currently the demand for foreign products, especially halal-certified food or beauty products, is in great demand abroad because it is considered that the goods to be consumed have standardization and go through a very strict process so that they are considered safe for direct consumption can increase the export value of Indonesia in advancing MSME products, especially the halal industry which is currently increasing